The use of SQL and second generation database management systems for data processing and information retrieval in libraries - LEIGH, W; PAZ, N (Information technology and libraries, 1989)
Structured Query Language (SQL) is a database querying language that was codified as a standard by the American National Standards Institute. SQL is based on the relational modeling of data and is a language for retrieving subsets of the database according to search criteria. SQL is awkward as a direct interface for patron catalog searching. Free text and partial string search are possible with SQL, and this capability can accomplish keyword searching, although not without drawbacks. There are new SQL-interfacing products and techniques that can solve the problem of lack of direct SQL applicability to patron-user computing. A 2nd generation of database management systems has been spurred by SQL standardization. The orientation of these new systems is to distribute application on local area networks. Mainframe computer performance is made available at personal computer prices by this client-server architecture. This development has many implications for library computing.